Beneficial Treatment Outcomes of Severe COVID-19 Patients Treated Entirely in Primary Care Settings With Dexamethasone Including Regimen—Case Series Report - Vukoja, Damir; Jurić, Andrea; Erkapić, Zdravka; Pejić, Tomislav; Zovko, Željko; Juričić, Josipa; Pejić, Jelena; Ćorluka, Matea (Frontiers in Pharmacology, 2021)
Even in 2021, the COVID-19 disease still represents a major global health concern, especially in developing countries. The burden of this disease caused by a certain coronavirus (SARS-CoV-2), which affects primary respiratory but as well other organ systems, keeps rising as the pandemic continues. Primary health care centers are the first line where COVID-19 patients are managed and should be able to manage the vast majority of them successfully. In this paper, we present a case series and concept of beneficial management of even deteriorating and severe patients treated entirely in our primary health center. The management is based on well-timed and rational dexamethasone use, as well as on various other pharmacological and non-pharmacological treatments and interventions, and is supported by provided statistical data. According to the presented experience and positive outcomes achieved, it seems that even deteriorating and severe COVID-19 patients can be treated successfully to some point or even completely in primary care settings. This kind of approach could be particularly beneficial in conditions of overload of higher-level health care institutions.